2019
DOI: 10.29333/ojcmt/5952
|View full text |Cite
|
Sign up to set email alerts
|

Two Images of Russia in the British Political Mass Media Discourse of 1991 – 1993 and 2013 – 2019: Pragmastylistic Aspect

Abstract: The paper considers political mass media discourse as a persuasive dialogue in which a journalist makes his interlocutors accept a certain point of view. The desired mental reaction on the part of interlocutors can only be achieved through careful choice of ways of persuasion and especially linguistic means often influencing effectively the emotional sphere. The persuasion can be subject to ideological aims thus representing a definite object as positive or negative. The paper claims that such object as the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…The set of researches is devoted to problems of effective influence in a media discourse, creation of media presentations, producing media advertising for rendering successful influence on the addressee, semiotics of media advertising, verbal promotion of goods and services through media (Boeva-Omelechko et al, 2019;Dijk van, 1988Dijk van, , 1997Gishkaeva et al, 2018;Grimak, 2001;Harvey, 2011;Jamieson & Campbell, 1997;Lakoff & Johnson, 1980;Langacker, 1991;Morris, 1971;Orekhovskaya et al, 2019;Rein, 1982;Shirokikh, 2018;Stanton et al, 1991;Sukhareva & Karnaukhova, 1998;Tameryan et al, 2019;Tezer et al, 2019;Ukhova & Marycheva, 2012;Wierzbicka, 1991Wierzbicka, , 1992Zheltukhina et al, 2019, etc.). The presentation of goods is a meeting in the correspondence or internal look of the seller and the buyer for the purpose of representation of goods, its advantages and shortcomings, benefits which will be got by the potential buyer (Rules of holding presentation of goods, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The set of researches is devoted to problems of effective influence in a media discourse, creation of media presentations, producing media advertising for rendering successful influence on the addressee, semiotics of media advertising, verbal promotion of goods and services through media (Boeva-Omelechko et al, 2019;Dijk van, 1988Dijk van, , 1997Gishkaeva et al, 2018;Grimak, 2001;Harvey, 2011;Jamieson & Campbell, 1997;Lakoff & Johnson, 1980;Langacker, 1991;Morris, 1971;Orekhovskaya et al, 2019;Rein, 1982;Shirokikh, 2018;Stanton et al, 1991;Sukhareva & Karnaukhova, 1998;Tameryan et al, 2019;Tezer et al, 2019;Ukhova & Marycheva, 2012;Wierzbicka, 1991Wierzbicka, , 1992Zheltukhina et al, 2019, etc.). The presentation of goods is a meeting in the correspondence or internal look of the seller and the buyer for the purpose of representation of goods, its advantages and shortcomings, benefits which will be got by the potential buyer (Rules of holding presentation of goods, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research of functional, semantic and genre characteristics of advertising in terms of stylistics and discourse analysis, peculiarities of construction of advertising text and its semantic and pragmatic organization, use of verbal and non-verbal signs, advertising name, etc. (Dijk van, 1988;Dijk van, 1997;Kara-Murza, 1996;Kryukova, 2004;Kaftandzhiyev, 2005;Vartanova, 2006;Kirpicheva, 2007;Ukhova & Marycheva, 2012;Kalashaova, 2014;Naumova & Budnik, 2014;Aniskina & Ukhova, 2015;Busygina & Zheltukhina, 2015;Boeva-Omelechko et al, 2019;Tameryan et al, 2018a;2018b;2019b;Zhang et al, 2019;Zheltukhina et al, 2019, etc.). It is important to emphasize the fact that previously scientists have not analyzed Chinese medical and cosmetic media advertising in the cognitive and psychological aspect of the media effect on the recipient (Shmeleva, 2018;Volskaya et al, 2018 The hypothesis of the study is that Chinese medical and cosmetic media advertising has a direct effect, revealed in extralinguistic markers, including cognitive and psychological markers, not only on the recipient as a consumer of advertising products and advertising services, but also on Chinese linguoculture, which in turn affects the creation of medical and cosmetic advertising media.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The last decades of the 20th and 21st centuries demonstrate transformational processes in Russian politics (Boeva-Omelechko et al, 2019;Zheltukhina et al, 2020), which concern not only the political system, but also political discourse. In modern political media communication, the effect of the addressee on the addressee is to attract the attention of the addressee (Mironova, 2001), as well as to encourage him to purchase the advertised goods voting, i.e., "buy" a politician or political party.…”
Section: Introductionmentioning
confidence: 99%